The relationship between the genetic status of the Vrn-1 locus and the size of the root system in bread wheat (Triticum aestivum L.) - O. G. Smirnova; T. A. Pshenichnikova (Вавиловский журнал генетики и селекции)
One of the main ways to fine-tune the adaptive potential of wheat cultivars is to regulate the timing of flowering using the genes of the Vrn-1 locus, which determines the type and rate of development. Recently, with the use of introgression and isogenic lines of bread wheat, it was shown that this locus is involved in the genetic control of root length and weight both under irrigation and drought conditions. It turned out that the VrnA1 gene is associated with a significant decrease in the size of the root system in a winter genotype. The Vrn-A1 gene had the strongest effect on the reduction of the root system in comparison with the homoeoallelic genes Vrn-B1 and Vrn-D1. The aim of this work was to determine whether the allelic composition of the genes at the Vrn-1 locus affects the root size in seven spring cultivars and in two lines of bread wheat differing in flowering time under conditions of normal watering and drought. The research was carried out in a hydroponic greenhouse; drought was created at the tillering stage. In this work, we have shown that early flowering wheat cultivars with the dominant Vrn-A1а allele have more lightweight and shorter roots under normal watering conditions compared to the late flowering carriers of the dominant homoeoalleles Vrn-B1 and Vrn-D1. In drought conditions, the root length decreased insignificantly, but the weight of the roots significantly decreased in all genotypes, with the exception of Diamant 2. It has been hypothesized that the level of the transcription factor VRN-1 at the onset of drought may affect the size of the root system. The large variability in root weight may indicate the participation, in addition to the Vrn-1 locus, of other gene networks in the formation of this trait. Breeders working to develop early maturing varieties should consider the possibility of reducing the root size, especially in arid conditions. A significant increase in the root size of line 821 with introgressions into chromosomes 2A, 2B, and 5A from T. timopheevii indicates the possibility of using congeners as a source of increasing the trait in wheat.